2015
DOI: 10.7554/elife.06203
|View full text |Cite
|
Sign up to set email alerts
|

Female mice ultrasonically interact with males during courtship displays

Abstract: During courtship males attract females with elaborate behaviors. In mice, these displays include ultrasonic vocalizations. Ultrasonic courtship vocalizations were previously attributed to the courting male, despite evidence that both sexes produce virtually indistinguishable vocalizations. Because of this similarity, and the difficulty of assigning vocalizations to individuals, the vocal contribution of each individual during courtship is unknown. To address this question, we developed a microphone array syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
255
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(281 citation statements)
references
References 84 publications
(112 reference statements)
20
255
6
Order By: Relevance
“…We also recommend to always use introduced mice from the same strain when testing mice from a mutant strain and to analyze the data as a pair of mice vocalizing. One recent study promotes the use of triangulation to localize the emitter 31 . In this study, females were found to also emit ultrasonic vocalizations during encounters with a male.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend to always use introduced mice from the same strain when testing mice from a mutant strain and to analyze the data as a pair of mice vocalizing. One recent study promotes the use of triangulation to localize the emitter 31 . In this study, females were found to also emit ultrasonic vocalizations during encounters with a male.…”
Section: Discussionmentioning
confidence: 99%
“…The rigorous assignation of calls to specific animals in a group of calling individuals remains a challenge (Janik et al, 2000;Gill et al, 2015;Neunuebel et al, 2015), but a comprehensive recording of subglottal pressure and/or EMG activity together with sound allows an unambiguous interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…As with lighting, avoiding reflections of the audio signal is good practice, which can be achieved by careful choice of chamber material (e.g. Neunuebel et al, 2015).…”
Section: Optimizing For High-quality Behaviormentioning
confidence: 99%
“…1E (Ohayon et al, 2013). To prevent animal-animal occlusions, animals can be restricted to a planar environment by using walls and/or lids they cannot climb (Mersch et al, 2013;Neunuebel et al, 2015;Simon and Dickinson, 2010), thereby removing occlusions due to visually overlapping positions on different surfaces (e.g. one animal on the ceiling and one under it on the floor).…”
Section: Avoiding Occlusionsmentioning
confidence: 99%